Upstream Competition and Open Access Regimes: Experimental Evidence - Niklas Horstmann; Jan Krämer; Daniel Schnurr (International Telecommunications Society (ITS), 2015)
We investigate the effects of alternative open access regimes on market performance. In particular, by means of an economic laboratory experiment we compare the market outcomes under unregulated wholesale competition, under a price-fixing rule (where firms must maintain their wholesale price for a fixed period of time), and under a margin squeeze rule (where the retail price of integrated firms must exceed their wholesale price). Our analysis suggests that wholesale and retail prices are substantially reduced by the introduction of a price-fixing rule at the upstream level compared to the unregulated scenario. In contrast, we do not find evidence that a margin squeeze regulation reduces retail market prices. In fact, while such a rule benefits the reselling firm by allowing for a viable profit margin, prices for consumers tend to be even higher than in the unregulated case.
Keywords: C92; L51; L90; 330; Next Generation Access Networks; Access Regulation; Open Access; Upstream Competition; Experimental Economics; Margin Squeeze